Positive electrode applied to alkaline nickel-zinc battery and preparation method of positive electrode

By adopting a combined structure of hydrophobic layer and micro-nanoparticle layer on the positive electrode of alkaline nickel-zinc battery, the problems of oxygen evolution side reaction and zinc corrosion are solved, and the charging and discharging efficiency and cycle life of the battery are improved, and the alkali retillation is avoided 'Phenomenon improves the overall performance and safety of the battery.

CN119297215APending Publication Date: 2025-01-10DONGGUAN CHAO BA BATTERIES CO LTD SHENZHEN INNOVATION CENTER
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411338647.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Alkaline nickel-zinc batteries are prone to oxygen evolution side reactions during charging and discharging, resulting in a decrease in the efficiency of charging and discharging, low utilization of active substances, intensified zinc corrosion and degradation of battery performance, and there is a 'alkali retiller' phenomenon, affecting safety and Cycle life.

Method used

The positive electrode consisting of a current collector and micro-nanoparticle layer is coated with a hydrophobic layer and micro-nanoparticle layer on the surface of the current collector. The liquid absorption and wetting properties are improved through the dry process, the interface impedance is reduced, and the side reactions of oxygen evolution are avoided. Add organic or inorganic binders to enhance electron transport and ion conduction capabilities.

Benefits of technology

It significantly improves the charging and discharge efficiency, discharge capacity, cycle life and rate performance of alkaline nickel-zinc batteries, reduces internal resistance, avoids zinc corrosion and "alkali retillery" phenomena, and improves the overall performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297215A_ABST
    Figure CN119297215A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode which comprises a current collector and a micro-nano particle layer, the surface of the current collector is coated with a hydrophobic layer, and the hydrophobic layer is coated with the micro-nano particle layer. And the thickness of the hydrophobic layer coated on the surface of the current collector is 10-300nm. Micro-nano particles in the micro-nano particle layer are dry powder particles, and the dry powder particles comprise micro-nano electrode active material nickel hydroxide and a micro-nano conductive agent, but do not comprise any organic or inorganic binder. The positive electrode has a porosity of about 10% to 50%. The invention also relates to a preparation method of the positive electrode and an application of the positive electrode in an alkaline nickel-zinc battery. The positive electrode prepared by the invention not only can effectively inhibit the oxygen evolution side reaction in the charge-discharge process and improve the coulombic efficiency, but also is helpful for improving the charge-discharge rate and cycle performance of the nickel-zinc battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of alkaline nickel-zinc batteries, and in particular to a positive electrode used in alkaline nickel-zinc batteries, and a method for preparing the positive electrode. Background Art

[0002] This section provides background information related to the present application which does not necessarily constitute prior art.

[0003] The positive electrode of an alkaline nickel-zinc battery usually contains nickel hydroxide Ni(OH) 2 (including its oxidized form nickel oxyhydroxide NiOOH), binders and functional metal oxide additives, and may also contain nickel metal, cobalt metal and / or cobalt compounds to enhance the conductivity of the positive electrode. The actual charge and discharge voltage window range of the prior art alkaline nickel-zinc battery is 1.2-1.9V, which is much higher than the theoretical voltage of 1.23V required for electrochemical water decomposition. Therefore, alkaline nickel-zinc batteries are prone to gasification side reactions during charge and discharge, especially in the Ni(OH) 2 Oxygen evolution side reaction occurs at the positive electrode and hydrogen evolution side reaction occurs at the negative electrode. The gas evolution side reaction not only causes the consumption of water in the alkaline electrolyte, causing the battery to dry up, further hindering the ion transmission inside the battery, but also causes a sharp increase in the gas pressure inside the battery, and even causes the "alkaline creep" phenomenon of alkaline nickel-zinc batteries.

[0004] Nickel hydroxide Ni(OH) in the positive electrode 2 As the main active material of alkaline nickel-zinc batteries, the following electrochemical reactions occur during the charging and discharging process:

[0005]

[0006] Among them, Ni(OH) 2 During the charging process, it is gradually oxidized and converted into NiOOH, releasing electrons and water. During the discharge process, NiOOH is reduced by electrons and converted into its initial state, Ni(OH). 2 Theoretically, Ni(OH) 2 The gram capacity can be as high as 289 mAh / g. In fact, in alkaline nickel-zinc batteries, Ni(OH) 2 The gram capacity of the active material is estimated to be only 210-240 mAh / g, and the corresponding active material utilization rate is: 72%-83%. It can be seen that the positive electrode Ni(OH) 2 There is still room for improvement in the utilization of active materials. The reason is that the positive electrode is mainly susceptible to the oxygen evolution side reaction. This process is mainly controlled by the following electrochemical reactions:

[0007] 4OH - →2H2 O+O 2 ↑+4e -

[0008] During the charging process of alkaline nickel-zinc batteries, the positive electrode should be Ni(OH) 2 The electrochemical conversion reaction of the active substance to NiOOH, however, in fact, the oxygen evolution side reaction will inevitably occur during charging. Generally speaking, when the alkaline nickel-zinc battery is charged with a constant current to 50%-75% of the full charge state, the charging voltage at this time is about 1.85-1.88V, and the positive electrode side is more prone to oxygen evolution side reaction. When the battery is fully charged, if the alkaline nickel-zinc battery continues to be charged at a constant voltage, the oxygen evolution side reaction of the positive electrode part will be seriously aggravated. Therefore, the oxygen evolution side reaction of the positive electrode will cause a decrease in the coulomb efficiency of charge and discharge. In other words, the oxygen evolution side reaction of the positive electrode will reduce the efficiency of the alkaline nickel-zinc battery in the energy storage and release process, resulting in a decrease in the utilization rate of the positive active material.

[0009] In addition, the charge and discharge coulomb efficiency of the positive electrode is also easily affected by the ambient temperature. Generally speaking, as the ambient temperature increases, the coulomb efficiency of the battery tends to decrease. The main reason is that at higher ambient temperatures, the oxygen evolution side reaction inside the battery is more serious. The gas evolution side reaction inside the battery has a potential destructive effect on the performance of alkaline nickel-zinc batteries, especially during constant voltage charging of alkaline nickel-zinc batteries, the oxygen evolution side reaction at the positive electrode will aggravate the zinc corrosion of the negative electrode in an alkaline environment. In this case, the zinc corrosion reaction can be expressed as follows:

[0010] 2Zn+4KOH+2H 2 O+O 2 →2K 2 Zn(OH) 4

[0011] The oxygen produced by the gassing side reaction at the positive electrode can easily penetrate the porous diaphragm, reach the negative electrode and start to react chemically with the charged metal zinc. This not only accelerates the local zinc dissolution reaction at the negative electrode, causing the loss of battery discharge capacity, but also generates soluble K 2 Zn(OH) 4 Among them, K 2 Zn(OH) 4The zincate ions can move freely in the alkaline electrolyte and can be easily reduced to metallic zinc during the charging process, which may cause deformation of the zinc negative electrode and even lead to the growth of zinc dendrites, seriously affecting the cycle life of the alkaline nickel-zinc battery. Most importantly, the freely movable zincate ions may randomly diffuse to the diaphragm with liquid absorption ability, or even migrate to the surface of the positive electrode. When the local pH environment of the electrolyte changes, the zincate ions have the opportunity to further transform into zinc oxide particles, thereby blocking the pore structure of the diaphragm or covering the surface of the positive electrode, causing the performance of the alkaline nickel-zinc battery to decline. Therefore, the oxygen evolution side reaction of the positive electrode will not only have an adverse effect on the negative electrode, but also indirectly affect the performance of the positive electrode, thereby causing a greater negative impact on the overall performance of the alkaline nickel-zinc battery.

[0012] As we all know, alkaline nickel-zinc batteries, as a potential aqueous rechargeable battery technology, have advantages such as high mass energy density (80-120Wh / kg), power density (≥1000W / kg) and intrinsic safety, and are expected to have broad application prospects in consumer electronics, power tools, industrial backup emergency power supplies, commercial energy storage, home energy storage, large-scale electrochemical energy storage and other fields. Alkaline nickel-zinc batteries for commercial use need to have low internal air pressure, high charge and discharge coulomb efficiency and long cycle life. It should be pointed out in particular that alkaline nickel-zinc batteries are required to be stored for at least one month or longer at extreme ambient temperatures (for example: 60°C). This requires avoiding excessive accumulation of air pressure inside the battery, which leads to the opening of the safety exhaust valve. This safety protection measure will bring the alkaline electrolyte to the positive electrode top cover through the pressure relief process, causing the "alkaline climbing" phenomenon of the alkaline nickel-zinc battery. This will not only cause a sharp "dive" in the performance of the alkaline nickel-zinc battery, but the "alkaline climbing" phenomenon can easily cause serious damage to electronic equipment.

[0013] Therefore, by improving the technology of the positive electrode of alkaline nickel-zinc batteries, the occurrence of gas evolution side reaction can be effectively suppressed, and the gas pressure inside the battery can be minimized. In addition, the negative electrode of alkaline nickel-zinc batteries is compared with Ni(OH) 2 The positive electrode has better conductivity and better discharge capacity (the theoretical gram capacity of ZnO is 658 mAh / g). Therefore, the electrochemical performance of alkaline nickel-zinc batteries, especially discharge capacity, rate performance and cycle life, is mainly limited by the electrochemical performance of the positive electrode. Summary of the invention

[0015] The present application aims to provide a positive electrode for alkaline nickel-zinc batteries. The alkaline nickel-zinc batteries using the positive electrode have high charge and discharge coulomb efficiency and high rate performance, and can significantly improve the mass energy density and cycle life of the alkaline nickel-zinc batteries. In addition, the alkaline nickel-zinc batteries using the positive electrode can effectively alleviate the zinc corrosion of the negative electrode and inhibit the gas evolution side reaction inside the battery, which is expected to completely solve the "alkaline creep" problem that occurs in the alkaline nickel-zinc battery during the charge and discharge process.

[0016] To achieve the above purpose, the present application adopts the following technical scheme: a positive electrode for alkaline nickel-zinc batteries, the positive electrode comprising a current collector and a micro-nano particle layer, the surface of the current collector is uniformly coated with a hydrophobic layer, and the micro-nano particle layer is coated on the hydrophobic layer. The thickness of the hydrophobic layer coated on the surface of the current collector is 10-300nm. It was unexpectedly found that when the thickness of the hydrophobic layer coated on the surface of the current collector is 10-300nm, the conductivity of the current collector coated with the hydrophobic layer on the surface only slightly decreases compared to the current collector not coated with the hydrophobic layer. When the thickness of the hydrophobic layer is greater than 300nm, the conductivity of the current collector coated with the hydrophobic layer on the surface begins to decrease significantly compared to the current collector not coated with the hydrophobic layer. Without sacrificing conductivity, the hydrophobic layer coated on the surface of the current collector can minimize the direct contact between the surface of the current collector and the water molecules in the alkaline electrolyte. This can not only significantly alleviate the corrosion of the high-concentration alkaline electrolyte on the current collector, but also effectively inhibit the occurrence of the oxygen evolution side reaction of the positive electrode.

[0017] In one or more embodiments, the current collector of the positive electrode is made of nickel foam, which includes nickel and / or nickel alloy, has a thickness of 300-800 μm, and a surface density of 280-420 g / m 2 .

[0018] In one or more embodiments, the current collector is obtained by depositing a nickel-based film on the surface of copper foam or titanium foam, and the nickel-based film can be prepared by a sol-gel method, a magnetron sputtering method, a thermal spraying method, an electrochemical deposition method, etc. The nickel-based film includes a compound having M1, M2, and a combination thereof, wherein M1 is nickel (Ni), and M2 is silver (Ag), titanium (Ti), gallium (Ga), aluminum (Al), zinc (Zn), germanium (Ge), tin (Sn), magnesium (Mg), barium (Ba), manganese (Mn), chromium (Cr), tungsten (W), or a combination thereof.

[0019] In one or more embodiments, the current collector needs to be pre-pressed to appropriately adjust the thickness of the nickel foam so as to meet the slurry drawing or coating process requirements of the positive electrode sheet.

[0020] The micro-nano particles in the micro-nano particle layer are dry powder particles, and the dry powder particles mainly include micro-nano electrode active material nickel hydroxide and micro-nano conductive agent. In one or more embodiments, the dry powder particles also include nano metal oxide additives and the like. Since no organic or inorganic binder is added, there is an appropriate particle spacing between the dry powder particles, so that the micro-nano particle layer of the positive electrode has a rich pore structure. By appropriately increasing the porosity of the positive electrode and reducing the specific surface energy of the positive electrode, the wettability between the positive electrode and the alkaline electrolyte can be effectively improved, so that the interface impedance between the positive electrode and the alkaline electrolyte can be effectively reduced. Most importantly, since no organic or inorganic binder is added, the electron transmission and ion conduction capabilities between the positive electrode active materials can be greatly improved. Therefore, the positive electrode provided by the present invention can effectively reduce the internal resistance of the alkaline nickel-zinc battery and improve the charge and discharge rate performance of the alkaline nickel-zinc battery.

[0021] In addition, since the micro-nanoparticles in the micro-nanoparticle layer are dry powder particles, this not only increases the liquid absorption and wettability of the alkaline electrolyte, but also prevents the agglomeration of the active material particles, which helps to improve the discharge capacity and cycle performance of the positive electrode.

[0022] The micro-nano particle layer of the present application does not contain organic or inorganic binders, which can not only improve the discharge capacity of alkaline nickel-zinc batteries, but also help to improve the electron transfer and ion conduction between active materials. As is well known, organic or inorganic binders themselves do not have electrochemical activity. They occupy a certain weight and volume in traditional positive electrodes, and mainly play the role of fixing active materials, conductive agents and functional additives in positive electrodes. Generally, the higher the amount of binder added, the more unfavorable it is for the improvement of the weight energy density and volume energy density of the battery, and the more unfavorable it is for reducing the production and manufacturing cost of the battery. In addition, binders usually use viscous organic compounds, such as sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), sodium alginate (Alg), sodium polyacrylate (SPA), polyethylene oxide (PEO), hydroxyethyl cellulose (HEC), hydroxypropyl methyl cellulose (HPMC), polytetrafluoroethylene (PTFE), etc. It is obvious that these organic substances have poor conductivity and may even increase the specific surface energy of the positive electrode, which is not conducive to electron transfer and ion transmission in the electrochemical process. By using a dry process without adding any organic or inorganic binder, not only can the charge transfer impedance of the alkaline nickel-zinc battery be reduced, but also the discharge capacity and rate performance of the alkaline nickel-zinc battery can be improved. At the same time, the hydrophobic layer and the micro-nano particle layer of the present application have good adhesion, which can effectively avoid the problem of active material shedding during the charge and discharge process of the alkaline nickel-zinc battery.

[0023] The micro-nano electrode active material is preferably a micron-sized spherical nickel hydroxide, and more preferably a micron-sized spherical nickel hydroxide with cobalt on the surface, which can be dissolved with zinc (Zn), cobalt (Co), magnesium (Mg), aluminum (Al), titanium (Ti), manganese (Mn), barium (Ba), tungsten (W), yttrium (Y), silver (Ag), silicon (Si), erbium (Er), lanthanum (La), cerium (Ce), calcium (Ca), ytterbium (Yb), niobium (Nb) and other elements. The particle size D50 of the micro-nano electrode active material is preferably 5-25μm, and more preferably 5-10μm. The preferred particle size distribution not only helps to improve the adhesion between the dry powder particles and the hydrophobic layer of the collector, but also improves the pore structure and electrochemical activity of the positive electrode, and helps to improve the liquid absorption of the positive electrode and the wettability between the alkaline electrolyte. It should be pointed out that the hydroxide ions in the alkaline electrolyte, as one of the important reactants in the charging and discharging process, help to increase the migration rate of hydroxide ions by increasing the liquid absorption and wettability of the positive electrode, thereby further improving the discharge capacity of the alkaline nickel-zinc battery.

[0024] In one or more embodiments, the micro-nano-scale electrode active material may be α-type nickel hydroxide and β-type nickel hydroxide, and β-type nickel hydroxide is further preferred. The primary structure of nickel hydroxide is a nanoparticle or nanosheet structure, the particle size of the nanoparticle is 50-300nm, and the thickness of the nanosheet is 20-100nm. The secondary structure of nickel hydroxide is a spherical structure.

[0025] The dry powder particles may also include a micro-nano conductive agent to further improve the electron transfer capacity of the positive electrode and reduce the contact resistance between the current collector and the micro-nano particle layer. The particle size D50 of the micro-nano conductive agent is preferably 0.05-10 μm, and more preferably 0.1-5 μm. The morphology of the micro-nano conductive agent can be exemplified by irregular micron particles, irregular nanoparticles, micron-sized spheres, nano-sized spheres, nanorods, nanofibers, nanotubes, nanosheets and other structures. Based on the total mass of the dry powder particles, the content of the micro-nano electrode active material is 80wt.%-99.5wt.%, and more preferably 90wt.%-96wt.%; the content of the micro-nano conductive agent is 0.5wt.%-20wt.%, and more preferably 1wt.%-5wt.%.

[0026] In one or more embodiments, the dry powder particles include a micro-nano conductive agent, which can also be a metal and a carbon-based material. Examples of metal materials include: metal silver powder, metal tungsten powder, metal zinc powder, metal nickel powder, metal indium powder, metal tin powder, and any combination thereof. Examples of carbon-based materials include: acetylene black, carbon nanotubes, graphite, graphene oxide, graphene, carbon fiber, and any combination thereof. Based on the total mass of the dry powder particles, the content of the micro-nano conductive agent is 0.5-20wt.%, and more preferably 1-5wt.%.

[0027] In one or more embodiments, the dry powder particles include a micro-nano conductive agent, which is a cobalt compound, such as cobalt trioxide, cobalt tetraoxide, cobalt sulfide, cobaltous oxide, cobalt hydroxide and / or cobalt oxyhydroxide. By forming a smooth conductive path between the micro-nano particle layers, the electron transfer speed and efficiency during the charge and discharge process of the alkaline nickel-zinc battery can be greatly improved. Based on the total mass of the dry powder particles, the content of the micro-nano conductive agent is 0.5wt.%-20wt.%, and more preferably 1wt.%-5wt.%.

[0028] In one or more embodiments, the dry powder particles include nano metal oxide additives, such as magnesium oxide, zinc oxide, aluminum oxide, silicon oxide, tungsten oxide, barium oxide, titanium oxide, calcium oxide, cerium oxide, lead oxide, dysprosium oxide, erbium oxide, ytterbium oxide, yttrium oxide, holmium oxide, samarium oxide, gadolinium oxide, lanthanum oxide, zirconium oxide, molybdenum oxide, manganese oxide, silver oxide, silicon oxide, nickel oxide and any combination thereof. It is worth mentioning that rare earth oxides can effectively inhibit the volume change and crystal structure change of the positive electrode active material nickel hydroxide during the charge and discharge process, which helps to improve the cycle stability and service life of the alkaline nickel-zinc battery. Based on the total mass of the dry powder particles, the content of the nano metal oxide additive is 0.5wt.%-10wt.%, and more preferably 1wt.%-5wt.%.

[0029] Micro-nano dry powder particles can be prepared by dry powder mixing, for example, a certain proportion of the selected micro-nano electrode active material nickel hydroxide, the selected micro-nano conductive agent and the selected nano metal oxide additive are uniformly mixed by grinding, mechanical stirring or ball milling. Micro-nano dry powder particles can also be prepared by wet mixing, for example, a certain proportion of the selected micro-nano electrode active material nickel hydroxide, the selected micro-nano conductive agent and the selected nano metal oxide additive are sequentially added to an excess of water solvent, and then fully ground, ball milled, air flow milled, ultrasonic dispersed and other treatment methods are carried out. By controlling the granulation conditions such as drying temperature and drying time, uniform micro-nano dry powder particles can be prepared.

[0030] The thickness of the positive electrode is preferably 300-800 μm, more preferably 450-700 μm; the thickness of the micro-nano particle layer is preferably 300-600 μm.

[0031] The porosity of the positive electrode is about 10%-50%, preferably 30-45%, for example 30%, 35%, 40%, 45%, etc. This porosity is conducive to enhancing the wetting effect of the alkaline electrolyte into the positive electrode. From the perspective of actual production and manufacturing, by increasing the wetting speed of the positive electrode into the alkaline electrolyte, the standing time after injection can be shortened, which helps to improve the production efficiency of the battery and reduce the manufacturing cost; from the perspective of battery performance, increasing the liquid absorption of the positive electrode and the wettability between the alkaline electrolyte can greatly increase the migration rate of the hydroxide ions in the alkaline electrolyte to the positive electrode. This can not only reduce the charge transfer impedance of the battery, but also help to improve the rate performance of the alkaline nickel-zinc battery charge and discharge. If the porosity is not within the above range, the mass energy density of the alkaline nickel-zinc battery will be reduced, and the rate performance and high and low temperature performance will decrease.

[0032] The positive electrode provided in the present application suppresses the oxygen evolution side reaction of the positive electrode, uses a dry process to improve the liquid absorption of the positive electrode and the wettability between the alkaline electrolyte, and reduces the corrosion of the high-concentration alkaline electrolyte on the current collector. On the one hand, it can effectively improve the coulombic efficiency of charge and discharge and avoid the increase of the internal gas pressure of the battery. On the other hand, it can also reduce the internal resistance of the alkaline nickel-zinc battery and improve the electron transmission and ion conduction capacity of the positive electrode. Therefore, the positive electrode provided in the present application can significantly improve the coulombic efficiency, discharge capacity, cycle life and charge and discharge rate performance of the alkaline nickel-zinc battery.

[0033] The present application also provides a method for preparing the positive electrode, comprising the following steps:

[0034] Step 1, coating a coating solution or coating slurry containing a hydrophobic agent on a current collector, and drying at high temperature to form a hydrophobic layer having hydrophobicity on the surface of the current collector;

[0035] Step 2: Dry powder particles containing micro-nano-scale electrode active materials are coated on the surface of the hydrophobic layer through a dry process to prepare a positive electrode.

[0036] The preparation method may further include performing a powder cleaning treatment on the surface of the positive electrode to completely remove the floating powder on the surface of the positive electrode and improve the safety performance of the positive electrode in use.

[0037] The preparation method may also include cutting the positive electrode, using die rolling, laser slitting, etc. to cut the positive electrode into a size that meets the battery design requirements.

[0038] The preparation method may also include kneading the positive electrode to improve the softness of the positive electrode and facilitate the winding packaging of the alkaline nickel-zinc battery.

[0039] The preparation method may also include a tab welding process for the positive electrode, where a metal nickel sheet or a stainless steel nickel-plated strip is directly welded to the positive electrode sheet to ensure good electrical connection between the positive electrode sheet and the positive electrode top assembly, which can be further assembled into an alkaline nickel-zinc battery.

[0040] In general, the amount of hydrophobic agent used in the preparation of the positive electrode should be sufficient to provide sufficient hydrophobicity to the surface of the current collector. The hydrophobicity of the hydrophobic agent can be characterized by its surface tension, for example, by measuring the static contact angle of deionized water on a smooth surface coated with the hydrophobic agent. The use of a hydrophobic agent can produce a hydrophobic surface characterized by a static contact angle of at least 90° for deionized water.

[0041] The hydrophobic agent can select coupling agents of different compositions, especially fluorine-containing coupling agents. Fluorine-containing coupling agents, such as perfluoroalkyl silane, fluoroallyl silane, etc., ensure the formation of a strong interface bond between the current collector and the dry powder particles through their unique chemical stability and low surface energy, thereby improving the cycle stability of alkaline nickel-zinc batteries. In addition, other commonly used coupling agents include silane coupling agents (for example: vinyl triethoxy silane), titanate coupling agents (for example: isopropyl triacetoxy titanate), zirconate coupling agents (for example: isopropyl zirconate), aluminate coupling agents (for example: triacetate aluminate) and phosphate coupling agents (for example: triethyl phosphate).

[0042] In order to further enhance the adhesion between the hydrophobic layer and the dry powder particles, the preferred hydrophobic agent is selected from fluorinated polymers (i.e., polymer materials containing at least one fluorine atom). Non-limiting examples of available fluorinated polymers include at least one of the following materials: fluorinated ethylene propylene, perfluoroalkoxy polymer resins, methyl fluorinated alkoxy polymer resins, polychlorotrifluoroethylene, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, ethylene-chlorotrifluoroethylene copolymers. In addition, copolymers of fluorinated polymers may also be included, such as copolymers of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride, polyhexafluoropropylene, tetrafluoroethylene hexafluoropropylene copolymers, alkoxy fluorinated vinyl copolymers, ethylene-tetrafluoroethylene copolymers, or combinations thereof.

[0043] In one or more embodiments, based on the total mass of the coating solution, the content of the hydrophobic agent is 0.1 wt.%-10 wt.%, the drying temperature for forming the hydrophobic layer is 60-200° C., and the thickness of the hydrophobic layer is 10-300 nm.

[0044] In one or more embodiments, based on the total mass of the coating slurry, the content of the hydrophobic agent is 0.1wt.%-10wt.%, the content of the conductive agent is 1wt.%-5wt.%, the drying temperature for drying to form a hydrophobic layer is 200-350°C, and the thickness of the hydrophobic layer is 10-300nm. The coating slurry is formed by uniformly mixing conductive particles, such as but not limited to carbon, with a hydrophobic agent, and the coating slurry may also contain a solvent and a surfactant, and the weight ratio of the conductive particles to the hydrophobic agent in the coating slurry may be in the range of 1:4-9. Any application method may be used to apply this coating slurry directly to the surface of the current collector. Certain non-limiting examples of the application method for applying the coating slurry include, but are not limited to, blade coating, ultrasonic spraying, and dip coating. After high-temperature drying, the coating slurry can remove all solvents, thereby forming a hydrophobic layer with a certain conductivity on the surface of the current collector.

[0045] The dry process of attaching dry powder particles to the pores of the current collector and the surface of the hydrophobic layer can adopt methods known to those skilled in the art, such as: powder spraying, electrostatic spraying, thermal spraying, powder printing, roller printing, drum printing, fluidized bed dip coating, electrostatic fluidized bed coating, etc. Since the micro-nano particle layer does not contain any organic or inorganic binder, the dry process of the present application is preferably powder spraying, which can achieve uniform coating of micro-nano dry powder particles in the pores of the current collector and on the surface of the hydrophobic layer. In one or more embodiments, the baking temperature of the powder spraying is 90-150°C, for example: 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, etc. The baking time is 1-60min, preferably 5-20min.

[0046] In one or more embodiments, the pressing after baking is performed by roller pressing, and the process parameters of the roller pressing include: B / C roller speed ratio 1: 1-2; B roller is a rough roller with a roughness of 0.2-0.5 μm; C roller is a rough roller with a roughness of 0.6-0.9 μm. The applied roller pressure is very important for the adhesion between the dry powder particles (micro-nano-level electrode active material nickel hydroxide, micro-nano-level conductive agent and nano metal oxide additive) and the current collector. In general, increasing the roller pressure helps to increase the compaction density of the positive electrode, promote the electron transport of the positive electrode, improve the volume energy density of the alkaline nickel-zinc battery, and achieve higher discharge capacity, charge and discharge rate and cycle performance. When the roller pressure is too high (60T), it not only causes the particles of the active material (spherical nickel hydroxide) in the positive electrode sheet to break, but also greatly reduces the porosity of the positive electrode, which is not conducive to the alkaline electrolyte to penetrate into the positive electrode sheet to participate in the electrochemical reaction, and may even damage the hydrophobic layer coated on the surface of the current collector. Therefore, the applied roller pressure is preferably 10-50T, preferably 20-40T.

[0047] In one or more embodiments, the pressing after baking is performed by hot pressing, and the temperature of hot pressing is 100-300°C and the pressure is 1-10MPa. Hot pressing can significantly enhance the adhesion between the dry powder particles and the current collector, and can further improve the discharge capacity, charge and discharge rate and cycle performance of the alkaline nickel-zinc battery. The temperature of hot pressing is preferably 150-180°C, and the pressure is preferably 4-8MPa.

[0048] In one or more embodiments, the thickness of the prepared positive electrode is 300-800 μm and the compaction density is 2.0-4.5 g / cm 3 , preferably 3.0-4.0g / cm 3 .

[0049] The present application prepares the positive electrode by a combination of dry and wet methods. Specifically, a hydrophobic layer is prepared on the surface of the current collector by a wet method, and at the same time, a powder spraying method is used to replace the positive electrode slurry of the traditional wet method with dry powder particles, without adding any organic or inorganic binder, to achieve a close combination of micro-nano-level electrode active materials and the current collector hydrophobic layer, significantly improving the performance of alkaline nickel-zinc batteries.

[0050] In this application, if a 10-300nm hydrophobic layer is not prepared on the current collector surface in advance, and the dry powder particles are directly coated on the current collector surface by a pure dry method, the bonding between the micro-nano electrode active material and the current collector will be weak. More importantly, since the alkaline electrolyte can also directly contact the surface of the current collector, the oxygen evolution side reaction of the positive electrode begins to intensify, and the current collector is more susceptible to the corrosion of the high-concentration alkaline electrolyte, resulting in poor charge and discharge coulomb efficiency, battery internal pressure and cycle performance of the alkaline nickel-zinc battery.

[0051] The manufacturing process of the positive electrode provided in the present application is simple and easy to realize large-scale industrialization. In addition, since no organic or inorganic binder is added, it not only helps to improve the comprehensive performance of the alkaline nickel-zinc battery, especially the coulomb efficiency of charge and discharge, battery energy density and charge and discharge rate performance, but also can reduce the production cost of the alkaline nickel-zinc battery.

[0052] Another object of the present application is to provide an alkaline nickel-zinc battery containing the above-mentioned positive electrode, including a battery housing and a battery cell and an alkaline electrolyte located in the battery housing; the battery cell includes a positive electrode, a negative electrode and a separator between the positive and negative electrodes. Among them, the positive electrode is the positive electrode provided in the present application, the negative electrode is a negative electrode containing an active substance (including zinc oxide, metallic zinc powder), and the separator is a porous membrane made of polyethylene (PE) and polypropylene (PP) plastics with strong liquid absorption ability and anti-zinc dendrite function, and its surface can be sulfonated, grafted, treated with surfactant hydrophilicity or plasma. The alkaline nickel-zinc battery has a high discharge capacity and good rate performance and cycle stability. The alkaline nickel-zinc battery exhibits a good capacity retention rate when charged and discharged under 0.5C / 0.5C conditions.

[0053] It should be noted that the positive electrode provided in the present application is not only applicable to alkaline nickel-zinc batteries, but can also be used in other alkaline battery systems, such as alkaline nickel-cadmium batteries, alkaline nickel-metal hydride batteries, alkaline nickel-iron batteries, etc.

[0054] The following describes the invention in conjunction with specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] The accompanying drawings further illustrate the present application, but the embodiments in the accompanying drawings do not constitute any limitation to the present application.

[0056] Figure 1 The conductivity results of the nickel foam current collector provided in Example 1 and Comparative Example 1 of the present invention.

[0057] Figure 2 FE-SEM surface morphology of the nickel foam current collector provided in Example 1 of the present invention ( Figure 2 (a) is the surface morphology image at 170 times; Figure 2 (b) is a surface morphology image at 1000 times magnification).

[0058] Figure 3 FE-SEM surface morphology of the nickel foam current collector provided in Comparative Example 1 of the present invention ( Figure 3 (a) is the surface morphology image at 170 times; Figure 3 (b) is a surface morphology image at 1000 times magnification).

[0059] Figure 4 FE-SEM cross-sectional view of the positive electrode provided in Example 1 of the present invention ( Figure 4 (a) is a cross-sectional view at 154 times magnification; Figure 4 (b) is a cross-sectional view at 1000 times magnification).

[0060] Figure 5 FE-SEM cross-sectional view of the positive electrode provided for Comparative Example 2 of the present invention ( Figure 5(a) is a cross-sectional view at 150 times magnification; Figure 5 (b) is a cross-sectional view at 1000 times magnification).

[0061] Figure 6 This is a static contact angle measurement diagram between the positive electrode provided in Example 1 of the present invention and the alkaline electrolyte.

[0062] Figure 7 This is a static contact angle measurement diagram between the positive electrode and the alkaline electrolyte provided in Comparative Example 2 of the present invention.

[0063] Figure 8 Oxygen evolution potential diagram of the foamed nickel current collector provided in Example 1 of the present invention and the foamed nickel current collector provided in Comparative Example 1.

[0064] Fig. 9 This is a performance test diagram of an alkaline nickel-zinc battery made using the positive electrode provided in Example 1 of the present invention ( Fig. 9 (a) is the charge-discharge curve for the first five cycles; Fig. 9 (b) is the discharge capacity; Fig. 9 (c) is the discharge platform voltage). DETAILED DESCRIPTION

[0065] It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0066] It should be noted that "hydrophobicity" as described in this application refers to a surface, film or coating that is difficult to wet with water. If a surface exhibits a static water contact angle of at least 90°, the surface is considered to be hydrophobic; if a surface exhibits a static water contact angle of at least 110°, the surface is considered to be very hydrophobic. The term "superhydrophobic" refers to a surface, film or coating that is extremely difficult to wet with water. A superhydrophobic surface, film or coating will typically have a static water contact angle of more than 130°.

[0067] It should be noted that the test method for the porosity of the positive electrode described in this application is as follows:

[0068] Step 1: Use tweezers to select at least 20 positive electrode discs with good appearance and no powder falling off the edges and put them into the sample cup, and record the number of positive electrode discs. Place the sample cup in the true density tester, which is a closed test system. Helium is introduced according to the program. The pressure of the gas in the sample chamber and the expansion chamber is detected, and the real volume V1 is calculated according to the ideal gas state equation (PV=nRT), where P is the pressure (Pa) and V is the gas volume (m 3 ), T is temperature (K), n is the amount of substance in the gas (mol), and R is the molar gas constant;

[0069] Step 2: Calculate the apparent volume V2 of the positive electrode disc, V2 = S × H × A, where S is the area of ​​a single positive electrode disc (in cm 2 ), H is the thickness of a single positive electrode disc (in cm), and A is the number of positive electrode disc samples;

[0070] Step 3: Porosity calculation method: Porosity P = (V2-V1) / V2×100%, where V1 is the true volume of the sample tested (in cm 3 ), V2 is the apparent volume of the sample (in cm 3 ).

[0071] It should be noted that the alkaline nickel-zinc battery involved in the present application includes a zinc negative electrode, a positive electrode, a separator, an alkaline electrolyte and a shell, the shell is used to accommodate the above components, and the positive electrode is the positive electrode provided in the present application. Among them, the zinc negative electrode is the negative electrode of the alkaline nickel-zinc battery, and the zinc negative electrode includes a negative electrode active material and a negative electrode current collector. The negative electrode active material includes a zinc compound, usually nano zinc oxide and / or metallic zinc powder, and other electrochemically active zinc compounds such as calcium zincate, zinc carbonate, zinc hydroxide can also be used. It is also possible to use zinc compounds with carbon coating on the surface, graphene-coated zinc compounds or carbon nanotube-modified zinc compounds. In addition to zinc oxide and metallic zinc powder, the zinc negative electrode may include other functional materials that promote specific processes in the zinc negative electrode, such as: enhancing ion conduction, promoting electron transfer, increasing the amount of liquid absorbed by the zinc electrode and the wettability between the alkaline electrolyte, inhibiting the solubility of the active material in the alkaline electrolyte, improving the corrosion resistance of metallic zinc, inhibiting the hydrogen evolution side reaction of the zinc electrode, inhibiting the deformation of the zinc negative electrode, and controlling the growth direction of zinc dendrites. For example, in some embodiments, the negative electrode active material may also include another metal oxide, such as bismuth oxide, barium oxide, magnesium oxide, aluminum oxide, lead oxide, indium oxide, zirconium oxide, titanium oxide, iron oxide, tin oxide, cerium oxide, calcium oxide, silicon oxide, or a combination thereof. Among them, bismuth oxide and indium oxide help to inhibit the hydrogen evolution side reaction of the zinc electrode and improve the electron transmission capacity of the zinc electrode.

[0072] The negative electrode current collector may be selected from at least one of copper, brass, phosphor copper, zinc and tin. The negative electrode current collector may be provided in various structural forms, including perforated metal strips, metal diagonal nets, punched metal foils, perforated metal plates, metal wire meshes, burr nets and foamed metals. For zinc electrodes, the negative electrode current collector is preferably copper or copper alloy in the form of perforated metal foil or metal diagonal nets. In some embodiments, the negative electrode current collector may also be coated with tin (Sn), lead (Pb), bismuth (Bi), silver (Ag), titanium (Ti), aluminum (Al), indium (In), molybdenum (Mo) or other coatings that are more compatible with zinc. In addition, the metal coating needs to have higher conductivity, hydrogen evolution overpotential and corrosion resistance. These metal coatings can be coated on the surface of the negative electrode current collector by methods well known to those skilled in the art, such as electroplating, immersion in molten metal, thermal spraying, chemical plating, magnetron sputtering and the like.

[0073] The binder of the zinc negative electrode can be selected from polytetrafluoroethylene emulsion (PTFE), styrene-butadiene rubber emulsion (SBR), polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC), sodium alginate (Alg), hydroxypropyl methylcellulose (HPMC), polyethylene oxide (PEO), hydroxyethyl cellulose (HEC), sodium polyacrylate (SPA), polyacrylic acid (PAA), β-cyclodextrin, sodium starch phosphate, hydroxypropyl starch, gelatin and xanthan gum, etc.

[0074] In addition, the diaphragm of the alkaline nickel-zinc battery is mainly used to ensure the insulation between the positive electrode and the zinc negative electrode, while allowing smooth ion transfer between the positive electrode and the zinc negative electrode. At the same time, the diaphragm can also block the zinc dendrites of the negative electrode from reaching the positive electrode, preventing short circuits inside the battery and causing failure of the alkaline nickel-zinc battery. Usually, the thickness of the alkaline nickel-zinc battery diaphragm is 100-300μm, and it can be prepared using nylon-based materials and microporous polyolefins (such as polyethylene and polypropylene). Among them, the diaphragm with a micron pore size can be used to increase the liquid absorption of the alkaline electrolyte; the diaphragm with a nanopore size can be used to prevent zinc dendrites from piercing the diaphragm. Because nylon-based materials and microporous polyolefins have a certain hydrophobicity, their surfaces need to be hydrophilically treated (such as grafting treatment, sulfonation treatment, surfactant treatment, plasma treatment) before they can be actually applied to alkaline nickel-zinc battery systems.

[0075] Wherein, the alkaline electrolyte contains alkali metal hydroxide. The electrolyte containing alkali metal hydroxide is dissolved in deionized water to be used as an alkaline nickel-zinc battery. As examples of alkali metal hydroxides, potassium hydroxide, sodium hydroxide, lithium hydroxide, etc. can be cited. In order to alleviate the dissolution and corrosion problems of zinc oxide and metallic zinc in alkaline electrolytes, compounds such as zinc oxide, calcium oxide, aluminum oxide, magnesium oxide, barium oxide, lead oxide, silicon dioxide, zinc hydroxide, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, and barium hydroxide can be added to the alkaline electrolyte. The mass ratio of potassium hydroxide, sodium hydroxide and lithium hydroxide is 10-30:1-10:1. The preferred concentration of hydroxide ions in the electrolyte is 6-16mol / L, preferably 8-14mol / L. Because the high-concentration electrolyte in this range can provide a sufficient amount of hydroxide ions to participate in the electrochemical reaction on the one hand, and on the other hand, it can improve the ionic conductivity inside the alkaline nickel-zinc battery, which helps to reduce the internal resistance of the battery and improve the discharge rate performance.

[0076] [Example 1]

[0077] This embodiment provides a positive electrode, and the preparation method of the positive electrode includes the following steps:

[0078] Step 1, mixing polytetrafluoroethylene in deionized water to prepare a coating solution, wherein the content of polytetrafluoroethylene in the coating solution is about 6wt.%;

[0079] Step 2: Prepare nickel foam (surface density: 280 g / m 2 ) is immersed in the coating solution for 10 minutes, then the nickel foam is slowly taken out and placed in a vacuum oven at 120°C for 1 hour. Thus, a hydrophobic layer can be formed on the surface of the nickel foam, and the thickness of the hydrophobic layer is about 80nm;

[0080] Step three, dry-mix the micro-nano-level electrode active material nickel hydroxide, the micro-nano-level conductive agent and the nano-metal oxide additive to prepare uniform dry powder particles. Based on the total mass of the dry powder particles, the content of micro-nano-level nickel hydroxide is about 94wt.%, the content of the micro-nano-level conductive agent is about 3wt.%, and the content of the nano-metal oxide additive is about 3wt.%. Among them, the micro-nano-level conductive agent is metallic nickel powder. Add the dry powder particles to a powder sprayer at a flow rate of 10g / min, and evenly spray the dry powder particles on the nickel foam coated with a hydrophobic layer to obtain a semi-finished product;

[0081] Step 4: hot-press the semi-finished product to prepare a positive electrode, wherein the hot-pressing temperature is 150° C., the hot-pressing time is 60 seconds, the hot-pressing pressure is about 8 MPa, and the thickness of the positive electrode is about 450 μm.

[0082] [Example 2]

[0083] This embodiment provides a positive electrode, and the preparation method of the positive electrode includes the following steps:

[0084] Step 1, mixing a perfluoroalkoxy polymer resin in anhydrous ethanol to prepare a coating solution, wherein the content of the perfluoroalkoxy polymer resin in the coating solution is 8 wt.%;

[0085] Step 2: Prepare nickel foam (surface density: 280 g / m 2 ) is immersed in the coating solution for 15 minutes, then the nickel foam is slowly taken out and placed in an oven at 100°C for 30 minutes. Thus, a hydrophobic layer can be formed on the surface of the nickel foam, and the thickness of the hydrophobic layer is about 150nm;

[0086] Step three, dry-mix the micro-nano-level electrode active material nickel hydroxide, the micro-nano-level conductive agent and the nano-metal oxide additive to prepare uniform dry powder particles. Based on the total mass of the dry powder particles, the content of micro-nano-level nickel hydroxide is about 94wt.%, the content of the micro-nano-level conductive agent is about 3wt.%, and the content of the nano-metal oxide additive is about 3wt.%. Among them, the micro-nano-level conductive agent is metallic nickel powder. Add the dry powder particles to a powder sprayer at a flow rate of 5g / min, and evenly spray the dry powder particles on the nickel foam coated with a hydrophobic layer to obtain a semi-finished product;

[0087] Step 4: hot-press the semi-finished product to prepare a positive electrode, wherein the hot-pressing temperature is 120° C., the hot-pressing time is 45 seconds, the hot-pressing pressure is about 10 MPa, and the thickness of the positive electrode is about 500 μm.

[0088] [Example 3]

[0089] This embodiment provides a positive electrode, and the preparation method of the positive electrode includes the following steps:

[0090] Step 1, mixing a methyl fluoride alkoxy polymer resin in acetone to prepare a coating solution, wherein the content of the methyl fluoride alkoxy polymer resin in the coating solution is about 5 wt.%;

[0091] Step 2: Prepare nickel foam (surface density: 320 g / m 2 ) is immersed in the coating solution for 20 minutes, then the nickel foam is slowly taken out and placed in a vacuum oven at 180°C for 1 hour. Thus, a hydrophobic layer can be formed on the surface of the nickel foam, and the thickness of the hydrophobic layer is about 100 nm;

[0092] Step three, dry-mix the micro-nano-level electrode active material nickel hydroxide, micro-nano-level conductive agent and nano-metal oxide additive to prepare uniform dry powder particles. Based on the total mass of the dry powder particles, the content of micro-nano-level nickel hydroxide is about 94wt.%, the content of micro-nano-level conductive agent is about 3wt.%, and the content of nano-metal oxide additive is about 3wt.%. Among them, the micro-nano-level conductive agent uses metal nickel powder. Add the dry powder particles to the powder sprayer, adjust the voltage of the electrostatic generator to 55kV, control the flow rate pressure to 0.15MPa, spray distance to 200mm, powder output to 100g / min, atomization pressure to 0.3MPa and spray speed to 3.0m / min, and evenly spray the dry powder particles on the nickel foam coated with a hydrophobic layer to obtain a semi-finished product;

[0093] Step 4: hot-press the semi-finished product to prepare a positive electrode, wherein the hot-pressing temperature is 200° C., the hot-pressing time is 120 seconds, the hot-pressing pressure is about 4 MPa, and the thickness of the positive electrode is about 600 μm.

[0094] [Hydrophobicity test of hydrophobic layer]

[0095] The hydrophobicity test was performed on the hydrophobic layer formed in the process of preparing the positive electrode in Examples 1-3. After the hydrophobic layer was formed on the surface of the current collector, a deionized water droplet (the volume of the deionized water droplet was about 1 μL) was placed on the surface of the hydrophobic layer. The deionized water droplet was used to evaluate the hydrophobicity of the surface of the hydrophobic layer in a rolling grade range of 0, 1, 2 and 3, as follows:

[0096] 0-water droplet adheres to the hydrophobic surface;

[0097] 1-When tilted at 60°, the water droplet slides only in some parts;

[0098] 2-When tilted at 30°, the water droplet slides;

[0099] 3- When tilted at 5°, the water droplet slides completely in all sections.

[0100] The test results show that the hydrophobic layer formed on the surface of the positive electrodes prepared in Examples 1-3 provided by the present invention has a grade of 3.

[0101] [Comparative Example 1]

[0102] This comparative example provides a positive electrode. The difference between the preparation method of the positive electrode and the preparation method of the positive electrode provided in Example 1 is that no hydrophobic layer is formed on the surface of the nickel foam.

[0103] [Comparative Example 2]

[0104] This comparative example provides a positive electrode, and the preparation method of the positive electrode includes the following steps: adding micro-nano-scale electrode active material nickel hydroxide, micro-nano-scale conductive agent, polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR) and nano-metal oxide additives into deionized water in sequence. Among them, the nano-metal oxide additive is metal nickel powder. The mass ratio of nickel hydroxide, metal nickel powder, PTFE, SBR and nano-metal oxide is 90:4:2:2:2. A planetary vacuum mixer can be used to form a stable and uniform positive electrode slurry. Using the wet slurry drawing process, the positive electrode slurry is evenly coated on the foamed nickel (surface density: 320g / m 2 ) surface and pores. The semi-finished product is vacuum dried at 150°C for 30 minutes to prepare the semi-finished product. The semi-finished product is roll-pressed at a pressure of about 30T to prepare the positive electrode. The thickness of the positive electrode is about 500μm.

[0105] [Test on the influence of hydrophobic layer on the conductive properties of current collector]

[0106] The current collectors provided in Example 1 of the present invention and Comparative Example 1 were compared using a conductivity tester to study the effect of the hydrophobic layer on the conductivity of the current collector. The test process includes: cutting the provided current collectors into the same size, installing electrodes and applying different pressures. By changing the applied pressure, the change in the conductivity of the current collector can be observed. Figure 1 As shown, by comparing the conductivity of the current collector provided in Example 1 and Comparative Example 1, the study found that the hydrophobic layer on the surface of the current collector did not affect the conductivity of the current collector. Under different pressure conditions, the conductivity of the current collector did not change by an order of magnitude, which is mainly closely related to the thickness of the hydrophobic layer on the surface of the current collector. Since the thickness of the hydrophobic layer on the surface of the current collector provided in Example 1 is only 80nm and is not completely dense, the thinner hydrophobic layer does not have a significant effect on the conductivity of the current collector, and it still has good electron transmission ability, and can be suitable as a current collector for the positive electrode sheet.

[0107] [Porosity test of positive electrode]

[0108] The porosity test of the positive electrodes prepared in Examples 1-3 showed that the porosity of the positive electrode corresponding to Example 1 was about 35%; the porosity of the positive electrode corresponding to Example 2 was about 30%; and the porosity of the positive electrode corresponding to Example 3 was about 40%.

[0109] [Surface morphology test]

[0110] The surface morphology of the nickel foam provided in Example 1 and Comparative Example 1 was observed using a field emission scanning electron microscope (FESEM). Figure 2 and Figure 3 As shown, Figure 2The nickel foam provided in Example 1, Figure 3 The nickel foam provided in Comparative Example 1. By comparison, it can be seen that although the surface of the nickel foam treated with hydrophobicity in Example 1 has a uniformly coated hydrophobic layer, due to the thin thickness of the coating layer, no obvious difference is observed under a field emission scanning electron microscope compared with the nickel foam provided in Comparative Example 1.

[0111] The surface morphology of the positive electrode provided in Example 1 and the surface morphology of the positive electrode provided in Comparative Example 2 were observed using a field emission scanning electron microscope (FESEM). Figure 4 and Figure 5 As shown, compared with the positive electrode prepared by the wet process in Comparative Example 2, the positive electrode prepared by the dry process adopted in Example 1 has a high porosity, which is conducive to the subsequent infiltration of the alkaline electrolyte, thereby improving the ion transmission performance, increasing the utilization rate of the active material, and improving the performance of the alkaline nickel-zinc battery. In addition, it can be observed that the dry powder particles are evenly dispersed on the surface of the hydrophobic layer, the dry powder particles and the hydrophobic layer are firmly combined, and there is no obvious powdering phenomenon.

[0112] [Contact angle test of positive electrode and static alkaline electrolyte]

[0113] In an environment with a temperature of 20-25°C and a humidity of ≤50% RH, 1 μL of alkaline electrolyte (the alkaline electrolyte is mainly deionized water, wherein the concentration of hydroxide ions is about 12 mol / L) is dripped onto the surface of the positive electrode provided in Example 1 and the surface of the positive electrode provided in Comparative Example 2 through a plastic quantifiable dropper, respectively. Wait for 20 seconds, take a photo, and then use ImageJ, digital image processing software, and contact angle measurement plug-in to process the photo. Use the best ellipse fitting result to measure the angle and obtain the angle between the static alkaline electrolyte and the positive electrode. Generally speaking, the smaller the angle, the more complete the infiltration, and the better the contact interface between the alkaline electrolyte and the positive electrode. The test results are as follows: Figure 6 and Figure 7 As shown, it can be seen that the positive electrode sheet prepared by the dry method has a better wetting effect on the alkaline electrolyte. This is because the electrode sheet prepared by the dry method does not introduce organic or inorganic binders, and there are certain gaps between the particles, which is conducive to the penetration and infiltration of the alkaline electrolyte. The organic binder added to the positive electrode sheet prepared by the wet method almost fills the gaps between the particles, which makes the wetting effect of the alkaline electrolyte much weaker than that of the electrode sheet prepared by the dry method. In addition, due to the addition of organic binders, the surface of the positive electrode sheet prepared by the wet method has a large specific surface energy, which is not conducive to the rapid infiltration of the alkaline electrolyte. Therefore, the positive electrode prepared by the preparation method provided by the present invention can significantly improve the wettability with the alkaline electrolyte.

[0114] [Oxygen evolution potential test of current collector]

[0115] In order to compare the oxygen evolution potential of the current collector with a hydrophobic layer on the surface in Example 1 of the present invention and the oxygen evolution potential of the current collector without a hydrophobic layer on the surface in Comparative Example 1, Hg / HgO was used as the reference electrode, Pt was used as the counter electrode, and the current collectors provided in Example 1 and Comparative Example 1 were used as working electrodes to construct a three-electrode electrochemical system in an alkaline electrolyte. The effect of the hydrophobic layer on the oxygen evolution potential of the current collector was further studied using linear sweep voltammetry (LSV). The voltage scan rate was set to 5mV / s, and the test range was 0-1V. Figure 8 As shown in the figure, under the same test conditions, the oxygen evolution potential of the current collector with surface hydrophobic treatment is significantly higher than that of the current collector without surface hydrophobic treatment. The reason is that the surface hydrophilicity of metal nickel is very good, and under high potential conditions, oxygen evolution side reaction is very easy to occur on its surface. Surface hydrophobic treatment can, to a certain extent, prevent the foam nickel current collector from directly contacting with water molecules and hydroxide ions in the alkaline electrolyte, thereby effectively inhibiting the occurrence of oxygen evolution side reaction.

[0116] [Preparation of alkaline nickel-zinc batteries]

[0117] Alkaline nickel-zinc batteries were prepared using the positive electrodes provided in Examples 1-3 of the present invention and the positive electrodes provided in Comparative Examples 1-2, respectively, as follows:

[0118] Step 1, preparing the positive electrode provided in Example 1-3 and the positive electrode provided in Comparative Example 1-2;

[0119] Step 2: Prepare the zinc electrode. Mix nano zinc oxide, metallic zinc powder, bismuth oxide, carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a planetary vacuum mixer at a mass ratio of about 80:10:6:2:2 to form a stable and uniform negative electrode slurry. The negative electrode slurry is evenly coated on both sides of the punched tin-plated copper foil, dried at 180°C for 30 minutes, and the zinc electrode is obtained through processes such as rolling, slitting, kneading, and ear welding. Among them, the thickness of the punched tin-plated copper foil is about 25μm. The zinc electrode has an active material layer about 400μm thick and a compaction density of about 3.5-4.5g / cm 3 .

[0120] Step three, set a diaphragm between the positive electrode and the zinc electrode, and after welding, lamination, winding, casing, injection, pitting, sealing, formation and other processes, an alkaline nickel-zinc battery can be obtained. Among them, the diaphragm used is a hydrophilic polypropylene non-woven fabric diaphragm with a thickness of about 150μm, the shell of the alkaline nickel-zinc battery is an AA-type battery shell, and the electrolyte used is an alkaline electrolyte. The alkaline electrolyte uses deionized water as the main solvent, and the resistivity of deionized water is about 18MΩ·cm. The concentration of hydroxide ions is about 12mol / L. The way to add the electrolyte is centrifuge injection.

[0121] [Electrochemical performance test of alkaline nickel-zinc batteries]

[0122] The prepared alkaline nickel-zinc battery was activated as follows:

[0123] As the first cycle of charge and discharge activation, the alkaline nickel-zinc battery prepared above was charged at a constant current of 0.1C to 1.9V, then charged at a constant voltage until the current dropped to 0.1C, and then discharged at a constant current of 0.2C to 1.3V.

[0124] Next, as the second cycle of charge and discharge activation, constant current charging was performed at a current value of 0.2C to 1.9V, followed by constant voltage charging until the current dropped to 0.1C, and then constant current discharge was performed at a current value of 0.2C to 1.3V.

[0125] Thereafter, as the third cycle of charge and discharge activation, constant current charging was performed at a current value of 0.5C to 1.9V, constant voltage charging was then performed to 0.1C, and then constant current discharge was performed at a current value of 0.5C to 1.3V.

[0126] The activated alkaline nickel-zinc battery was left at 25±5°C for 14 days, after which the cycle test was started, and the above-mentioned charge and discharge procedure for the third cycle was continued. Based on the charge and discharge data of the first cycle of the cycle test, the first discharge capacity and the first coulomb efficiency were determined, and the discharge capacity retention rate (%) of the alkaline nickel-zinc battery was calculated using the discharge capacity during the first charge and discharge cycle and the discharge capacity at the predetermined number of cycles. The test results are shown in Table 1.

[0127] Fig. 9 : is a comparison chart of the charge and discharge curves of the alkaline nickel-zinc battery corresponding to Example 1 in the first 5 charge and discharge cycles. Fig. 9 It can be seen that the alkaline nickel-zinc battery prepared by the positive electrode provided in Example 1 has good charge and discharge reversibility, a discharge platform voltage of about 1.65V and a high discharge capacity. The charge and discharge curves of the first 5 cycles are highly overlapped, indicating that the electrochemical reversibility is good. According to the charge and discharge performance of the first cycle, the alkaline nickel-zinc battery corresponding to Example 1 can achieve a discharge capacity of about 1450mAh under 0.5C / 0.5C conditions. In addition, the discharge capacity decays slowly in the first 100 cycles, and the coulomb efficiency basically remains ≥95%. More importantly, the discharge platform voltage of the alkaline nickel-zinc battery corresponding to Example 1 has hardly changed during the cycle. Therefore, the positive electrode provided by the present invention has a good effect of inhibiting the oxygen evolution side reaction, and at the same time has good charge and discharge coulomb efficiency and cycle stability.

[0128] Rate discharge performance: After activation and capacity separation, the prepared alkaline nickel-zinc battery was charged to 1.9V at a constant current of 0.5C at 25±5°C, then charged at a constant voltage until the current dropped to 0.1C, and then discharged to 1.3V at 0.5C, 1C, 2C and 3C respectively. The 1C, 2C and 3C rate discharge capacities were recorded, and the percentage (%) of the 0.5C rate discharge capacity was calculated. The test results are shown in Table 1.

[0129] As can be seen from Table 1, the alkaline nickel-zinc battery prepared using the positive electrode of Examples 1-3 has excellent rate discharge performance, and its discharge specific capacity at 3C is not less than 75% of the discharge specific capacity at 0.5C, and the capacity retention rate is not less than 75%, and the cycle performance can be significantly improved compared to the alkaline nickel-zinc battery prepared by the positive electrode of Comparative Example 1. According to the comparison of the test results of Examples 1-3 and Comparative Example 1-2, it is shown that directly coating dry powder particles by dry process without preparing a hydrophobic layer on the surface of the current collector, or coating dry powder particles by wet process on the current collector with a hydrophobic layer, will have a significant negative impact on the electrochemical performance of the alkaline nickel-zinc battery.

[0130] Table 1

[0131]

[0132] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0133] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A positive electrode, characterized in that: The positive electrode comprises a current collector and a micro-nano particle layer, the surface of the current collector is coated with a hydrophobic layer, and the micro-nano particle layer is coated on the hydrophobic layer; The thickness of the hydrophobic layer coated on the surface of the current collector is 10-300 nm; The micro-nano particle layer does not contain a binder, the micro-nano particles in the micro-nano particle layer are dry powder particles, and the dry powder particles include micro-nano electrode active substances; The positive electrode has a porosity of 10% to 50%.

2. The positive electrode according to claim 1, characterized in that The micro-nano electrode active material is micro-nano nickel hydroxide, and the particle size D50 of the micro-nano electrode active material is 5-25 μm.

3. The positive electrode according to claim 1, characterized in that The dry powder particles also include a micro-nano conductive agent, the particle size D50 of the micro-nano conductive agent is 0.05-10 μm, based on the total mass of the dry powder particles, the content of the micro-nano electrode active material is 80wt.%-99.5wt.%, and the content of the micro-nano conductive agent is 0.5wt.%-20wt.%.

4. The positive electrode according to claim 1, characterized in that The current collector is nickel foam, and the nickel foam includes nickel and / or nickel alloy.

5. A method for preparing a positive electrode according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, coating a coating solution or coating slurry containing a hydrophobic agent on the current collector, and drying at high temperature to form the hydrophobic layer on the surface of the current collector; Step 2: coating the dry powder particles containing the micro-nano electrode active material onto the surface of the hydrophobic layer through a dry process.

6. The method according to claim 5, characterized in that Based on the total mass of the coating solution, the content of the hydrophobic agent is 0.1 wt.%-10 wt.%, the drying temperature for forming the hydrophobic layer is 60-200° C., and the thickness of the hydrophobic layer is 10-300 nm.

7. The method according to claim 6, characterized in that The hydrophobic agent is selected from polytetrafluoroethylene, fluorinated ethylene propylene, perfluoroalkoxy polymer resin, methyl fluorinated alkoxy polymer resin, polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, ethylene-chlorotrifluoroethylene copolymer, copolymer of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride, polyhexafluoropropylene, tetrafluoroethylene hexafluoropropylene copolymer, alkoxy fluoride copolymer, ethylene-tetrafluoroethylene copolymer, or a combination thereof.

8. The method according to claim 6, characterized in that The hydrophobic agent is selected from fluorine-containing coupling agents, silane coupling agents, titanate coupling agents, zirconate coupling agents, aluminate coupling agents, phosphate coupling agents, or combinations thereof.

9. The method according to claim 5, characterized in that The dry process is powder spraying, the baking temperature of the powder spraying is 90-150° C., and the baking time is 1-60 minutes.

10. Use of the positive electrode according to any one of claims 1 to 4 in an alkaline nickel-zinc battery.

Citation Information

Patent Citations

  • Battery pole plate manufacturing method and battery pole plate manufactured by the method

    CN101399335A

  • Battery electrode, preparation method thereof and battery

    CN102054979A

  • Method for preparing cathode of metal-air battery, and metal-air battery

    CN105932301A

  • High-performance negative-electrode-free aqueous zinc metal battery based on composite layered negative electrode current collector

    CN115764005A

  • Nickel electrode and alkaline secondary battery employing the same

    KR1019990000634A